2011
DOI: 10.1158/1078-0432.ccr-10-2887
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Affitoxin: A Potent Therapeutic Agent for the Treatment of HER2-Overexpressing Tumors

Abstract: Purpose Cancers overexpressing the HER2/neu gene are usually more aggressive and are associated with poor prognosis. Although trastuzumab has significantly improved the outcome, many tumors do not respond or acquire resistance to current therapies. To provide an alternative HER2-targeted therapy, we have developed and characterized a novel recombinant protein combining an HER2-specific Affibody and modified Pseudomonas aeruginosa exotoxin A (PE 38), which, after binding to HER2, is internalized and delivered t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…Recently, we demonstrated for the first time the compatibility of the DARPin format with PE40 (here denoted ETA 00 ) to produce high yields of a potent anti-EpCAM fusion toxin (25). Because, however, these small recombinant proteins have an elimination half-life of hardly more than 10 minutes (25,30,31), which limits tumor localization, pharmacologic improvements are mandatory. PEGylation offers several advantages for biomedical compounds, including an increased hydrodynamic radius and serum stability, resulting in increased blood residence time due to decreased proteolysis, renal filtration, and liver clearance, and delayed recognition by the immune system (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated for the first time the compatibility of the DARPin format with PE40 (here denoted ETA 00 ) to produce high yields of a potent anti-EpCAM fusion toxin (25). Because, however, these small recombinant proteins have an elimination half-life of hardly more than 10 minutes (25,30,31), which limits tumor localization, pharmacologic improvements are mandatory. PEGylation offers several advantages for biomedical compounds, including an increased hydrodynamic radius and serum stability, resulting in increased blood residence time due to decreased proteolysis, renal filtration, and liver clearance, and delayed recognition by the immune system (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Liver enzyme tests on mice treated with HER2-affitoxin showed that the average alanine aminotransferase plasma level was three times higher than in control animals but that the aspartate aminotransferase ratio was less than 2. 115 No significant differences in alkaline phosphatase or bilirubin levels were observed.…”
Section: Emerging New Her2-directed Therapiesmentioning
confidence: 90%
“…The amino acid sequence of an affibody molecule is based on a portion of the Staphylococcus aureus protein A. Production of affitoxin was performed by Zielinski et al 114,115 by subcloning the PE38 toxin sequence into a HER2-affibody expression construct, transforming bacteria with the construct, and inducing expression of affitoxin by stimulating with isopropyl-beta-D-thiogalactopyranoside. Nickel-affinity (HisTrap HP; GE Healthcare, Hertfordshire, UK) and anion exchange columns were used to purify affitoxin from cell lysates.…”
Section: Emerging New Her2-directed Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another approach, the immune factor for the SPN toxin produced by Streptococcus pyogenes was suggested as a potential novel bactericidal agent [38]. An additional example is the recently engineered and promising anticancer agent derived by combining a modified Pseudomonas aeruginosa exotoxin A with a HER2-specific affibody, termed affitoxin [39]. Streptokinase, which is produced by streptococci, has been used to unclog arteries in patients suffering from stroke [40,41].…”
Section: Other Bacterial Toxins As Pharmaceuticalsmentioning
confidence: 99%